The Nutritional Quality of Forage Grass Changes Due to Changing Soil Chemistry Resulting from Different Land-Use Management in the Oroba Valley, Kenya - Isaboke, Job; Odipo, Osano; Humphrey, Olivier S.; Dowell, Sophia M.; Watts, Michael J. (African Journal of Education,Science and Technology (AJEST), 2023)
Threats from land degradation may escalate problems of inadequate food supply and poverty that already afflict the inhabitants of the Oroba Valley, Nandi County, Kenya. The steepness and inadequate application of good agricultural management systems expose the area to soil degradation, including erosion, depletion, and leaching of nutrients. Here, forage grass contributes to 60% of animal nutrient intake and this study investigated the macronutrient levels of forage grass from four differently managed farms and their vulnerability to soil erosion. Grass and soil were sampled from four differently managed plots in a randomised block design: plots 1 and 2 contained five sections (blocks), while plots 3 and 4 contained six sections. Grass samples were collected and analysed for five macronutrients (Mg, P, Ca, Cr, and Fe) by ICP-MS. Analysis of soils for characteristics of all soils from the pilot plots were classified as non-calcareous since their pH values range from 5.4 - 6.5. Organic matter (OM) distribution in the pilot plots depends on the amount of available plant reduces; most were cleared for animal consumption, as shown on the lower grounds of all pilot plots. The pH levels across the pilot plots dictated the distribution of macronutrients analysed in this study. Different plants have different optimum pH ranges for macronutrient uptake after considering all others around the plant's environment. Redistribution of macronutrients in the gradient of individual pilot plots majorly depends on the movement of soil by erosion. Results from the study have shown that different land management (erosion mitigated farmland and non-mitigated, newly farmed, and virgin land) affects the soil chemistry, hence changing grass's absorption regime for macronutrients to grass. For example, Mg, P, and Cr distribution variation between the mitigated and non-mitigated plots in the study. Macronutrients are essential for plant growth, health/resilience and yield; land degradation affects the soil chemistry and interrupts the natural balance of macronutrients input into the food chain leading to failure of achieving SDG 2 and 3 (Zero hunger, good health and wellbeing).